2013
DOI: 10.1515/jpm-2013-0211
|View full text |Cite
|
Sign up to set email alerts
|

Gestational weight gain according to number of fetuses in Japanese women

Abstract: Weekly maternal weight gain increases with increasing number of fetuses. Our figures may be useful for advising Japanese women with multifetal pregnancies regarding gestational weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…The net weight gains of 4.2 and 3.1 kg in the last 2 weeks and 1 week in women with P-PE accounted for approximately 34% and 25% of the total weight gain of 12.2 kg in pregnancy, respectively, while respective values of 1.6 and 1.3 kg in women with O-PE accounted for 12% and 9.6% of the total weight gain of 13.6 kg. As the mean±SD weekly weight gain, defined as (maternal weight at delivery−pre-pregnancy maternal weight)/(GW at delivery−2), is 0.26±0.12 kg for Japanese women with singleton pregnancies not complicated with pregnancy-induced hypertension,17 and weight gain in the last antenatal 2 weeks is 0.9±0.9 kg for otherwise healthy Japanese women with singleton pregnancies18; these results indicated that although oedema due to the accumulation of excess water in the interstitial space occurred in late pregnancy in P-PE and O-PE, its degree was greater in women with P-PE than in those with O-PE.…”
Section: Discussionmentioning
confidence: 99%
“…The net weight gains of 4.2 and 3.1 kg in the last 2 weeks and 1 week in women with P-PE accounted for approximately 34% and 25% of the total weight gain of 12.2 kg in pregnancy, respectively, while respective values of 1.6 and 1.3 kg in women with O-PE accounted for 12% and 9.6% of the total weight gain of 13.6 kg. As the mean±SD weekly weight gain, defined as (maternal weight at delivery−pre-pregnancy maternal weight)/(GW at delivery−2), is 0.26±0.12 kg for Japanese women with singleton pregnancies not complicated with pregnancy-induced hypertension,17 and weight gain in the last antenatal 2 weeks is 0.9±0.9 kg for otherwise healthy Japanese women with singleton pregnancies18; these results indicated that although oedema due to the accumulation of excess water in the interstitial space occurred in late pregnancy in P-PE and O-PE, its degree was greater in women with P-PE than in those with O-PE.…”
Section: Discussionmentioning
confidence: 99%
“…GWG may vary according to ethnicity. However, among 128838 and 5573 Japanese women with singleton and twin pregnancies, respectively, the numbers of women with GWG>20 kg, >25 kg and >30 kg were 1.1%, 0.20% and 0.06% for women with singleton pregnancies and 3.2%, 0.43%, and 0.09% for twin pregnancies, respectively [13]. Thus, three PPCM cases, including one in a previous pregnancy of the present case, were associated with greater GWG.…”
Section: Discussionmentioning
confidence: 55%
“…Average GWG reaches a pre-pregnancy body weight of approximately 20% [13], while the circulating blood volume physiologically increases in pregnancy by approximately 40% [14] and this natural volume overload leads to physiological cardiac hypertrophy [15]. However, in a mouse model, pathological hypertrophy (remodeling showing relative lack of capillary density with contractile dysfunction) can occur in the presence of sustained overload [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Gestational weight gain may vary according to ethnicity. However, among 128,838 Japanese women with singleton pregnancies, 10 the mean (SD) weekly weight gain was 0.26 (0.12) kg and total gestational weight gain was approximately 9.6 (4.4) kg. Median (2.…”
Section: Discussionmentioning
confidence: 99%